Whole genome resequencing identifies the CPQ gene as a determinant of ascites syndrome in broilers - Dey, Shatovisha (PLoS One, 2018)
BACKGROUND: Ascites syndrome is the most severe manifestation of pulmonary hypertension in fast-growing broilers. The disease can be attributed to increased body weights of birds, where the higher metabolic load is not matched by sufficient oxygen supply to the cells and tissues. Although there are environmental components, the disease exhibits moderate to high heritability. The current study uses high throughput whole genome resequencing (WGR) to identify genes and chromosomal regions associated with ascites. RESULTS: The WGR data identified the CPQ gene on chromosome 2. The association was confirmed by genotyping a large collection of DNAs from phenotyped birds from three distinct broiler lines using SNPs in intron 6 and exon 8 of the CPQ gene. By combining the genotype data for these two SNP loci, we identified three different alleles segregating in the three broiler lines. Particular genotypes could be associated with resistance to ascites. We further determined that particular genotypes most associated with resistance overexpress CPQ mRNA in three tissues which might explain the role of these alleles in contributing to resistance. CONCLUSIONS: Our findings indicate CPQ is an important determinant of pulmonary hypertension syndrome leading to ascites in broilers. We identified particular SNPs that can be used for marker-assisted selection of broilers for resistance to the disease. Our findings validate WGR as a highly efficient approach to map determinants contributing to complex phenotypic or disease-related traits. The CPQ gene has been associated with pulmonary hypertension in genome-wide association studies in humans. Therefore, ascites investigations in broilers are likely to provide insights into some forms of hypertension in humans.